Aktywność społeczno-polityczna kobiet na szczeblu lokalnym z uwzględnieniem sytuacji w gminie Gostyń po wyborach samorządowych 2010 r. - Karolczak, Karolina (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
Public and political activity of women – this subject has been constantly present in Polish public discourse for many years. Lately, the main part of this discourse is the matter of parity and legal guarantee of minimum 35% places dedicated to women on the elections candidates’ register. This essay assesses the legitimacy of these modifications with reference to necessity of cultural or social circumstances. The author also presents factors that determinate women’s public activity. All of these theoretical deliberations are referred to the situation in Gostyń commune and particularly to the personnel of the town council (it consists of only 19% of women).